Design and testing of bicyclic inhibitors of Grb7—are two cycles better than one?. Issue 5 (19th September 2013) - Gunzburg, Menachem J.; Ambaye, Nigus D.; Del Borgo, Mark P.; Perlmutter, Patrick; Wilce, Jacqueline A.; Craik, David J.
ABSTRACT Grb7 is an adapter protein involved in the propagation of signals in cancer cell migration and proliferation, and is thus a target for the development of novel anti‐cancer agents. An 11‐residue thioether‐cyclized peptide known as G7‐18NATE has previously been developed, that inhibits Grb7 via specific interactions with its SH2 domain with micromolar affinity. Here we explore whether the peptide binding is enhanced by the addition of a second linkage designed to restrain the peptide in its bound conformation and thus reduce the entropic loss upon binding. The use of an O‐ally ser covalent linkage between residue positions 1 and 8 successfully enhanced the affinity, and ITC showed that the entropic loss was reduced. A peptide with thioether‐cyclization exchanged for an amide linkage showed reduce affinity, though the formation of a disulfide bond between positions 1 and 8 in this peptide enhanced its binding. This study paves the way for improving the G7‐18NATE scaffold for second generation inhibitors of Grb7. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 543–549, 2013.